Прогнозування зміцнення державки твердосплавного різця в результаті загартування в полімерному середовищі після індукційного паяння - Дутка, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The numerical results of prognostication of the hardness and thickness of surface layer of the steel (35ХГСА) holder in results of the hardening in water solution of polymer Na–KMC and in machine oil I-20 at 20 ºС are presented. It is establish, that in polymer medium the cooling rate of the steel holder to temperature of start of the martensite transformation is in 2–3 times greater than in machine oil. But if cooling duration to temperature of termination of the martensite transformation is smaller than 70 c, than results of the hardening in polymer medium and in machine oil are practically identical. It is shown that one way to influence on results of the hardening may be the choice of the cooling duration in the air after induction heating.